Can immunofluorescence on Tzanck smear be used as a substitute for direct immunofluorescence on skin biopsy in diagnosis of pemphigus disease? - Shahidi Dadras, Mohammad; Asadi Kani, Zahra; Hamedani, Behnaz; Dadkhahfar, Sahar; Rastgoo, Nazy; Mozafari, Nikoo (Dermatology Practical & Conceptual, 2022)
Introduction:  Few studies have been conducted on the use of Direct Immunofluorescence (DIF) on skin/mucosal scraping smear for diagnosis of pemphigus disease; however, the diagnostic value of DIF on the smear has not been fully evaluated.Objectives: to assess the sensitivity and specificity of DIF on skin/mucosal smear for diagnose of pemphigus in the patients presenting with mucocutaneous erosive lesions.Methods: A total of 89 patients including 40 males and 49 females aged between 23 and 80 years old with various bullous disorders were enrolled in the study. For definite diagnosis, all the patients were subjected to lesional biopsy for pathological studies and perilesional biopsy for DIF studies. In all the cases, skin/mucosal scraping  smears were prepared from the perilesional healthy skin/mucosa and were stained with immunofluorescence conjugated anti-IgG.Results:Of 89 patients, 56 (63%) patients were diagnosed with pemphigus. Immunodeposits favoring the pemphigus were demonstrated in the 46 smears of 56 cases of pemphigus (sensitivity of 82%). No case with other types of bullous disease had positive DIF on the smear (specificity of 100%). Conclusion: The findings of the study showed that the sensitivity of DIF on the smear is not high enough to allow us replacing the conventional DIF with smear-DIF for diagnosis of pemphigus, while the specificity of 100% would allow the   unequivocal identification of a subset of patients with pemphigus.